Integration of Managerial Communications into the Strategic Marketing System of the Enterprise - Chepurko Anton Yu. (Bìznes Inform, 2025)
The development of a strategic approach to managing the communication activities of an enterprise includes identifying priority means of information influence and assessing their effectiveness in establishing and maintaining an efficient dialogue with target groups. Special attention is required for the rational structuring of the components of the communication complex, which ensures an increase in the competitiveness of the product offering and strengthens consumer loyalty to the brand. The aim of the present study is to theoretically substantiate and practically examine the mechanisms of integrating managerial communications into the strategic marketing system of the enterprise, considering the current challenges of the market environment. In the context of achieving the set aim, it is advisable to define the conceptual foundations for effective communication policy formulation, establish the interconnections between management communication and the implementation of marketing strategies, and propose a structured model of communication interaction within corporate governance. An integrated marketing communication system is viewed as a cohesive structure that includes a set of entities, information flows, and methods of message transmission, aimed at establishing stable, value-driven relationships with key audiences in executing strategic marketing objectives. The article reveals theoretical and methodological approaches to the integration of management communications into the structure of a company’s strategic marketing through the analysis, systematization, and generalization of scientific opinions on managing the company’s communication policy. The conceptual foundations for forming a communication policy as a tool for achieving marketing objectives have been systematized. A model has been proposed that ensures the integrity of communication impact within the marketing strategy, as well as adaptability to changes in the information landscape. The practical significance of the research lies in the potential application of the results to enhance the efficiency of management of interaction with stakeholders.